Revisiting the Resource–Conflict Link: A Systematic Comparative Test of Causal Mechanisms in Four Major Oil-Exporting Countries - Matthias Basedau; Annegret Mähler; Miriam Shabafrouz (German Institute of Global and Area Studies (GIGA), 2011)
Causal mechanisms and related contextual variables are crucial to the study of the resource-conflict link, but little systematic research has been done on their exact functioning. This paper contributes to the filling of this gap by comparing four major oil exporters (Algeria, Iran, Nigeria, and Venezuela) with differing levels of internal violence. To capture the causal complexity of the resource-conflict link we created a questionnaire with some 150 variables that distinguish between resource-specific (RS) and non-resource specific (NRS) conditions. The causal mechanisms are measured by assigning pertinent RS and NRS indicators to them. Our results suggest that the role of resources may be less prominent than is widely assumed. Only three resource-related causal mechanisms provide limited explanatory value (motive at subnational level, indirect economic, and institutional mechanism) by distinguishing Venezuela-the most peaceful case-from all the others. Only a mixed mechanism that combines 13 RS and NRS (economic and geographic characteristics, identity, intergroup relations, as well as political and institutional variables, including elite behavior) conditions can explain the differences between the countries with regard to the dependent variable comprehensively.
Keywords: 300; oil; violent conflict; causal mechanism; resource curse; Erdölvorkommen; Politischer Konflikt; Institutionelle Infrastruktur; Systemvergleich; Algerien; Nigeria; Iran; Venezuela